Progressive Muscle Relaxation and Health Education Based on the Theory of Planned Behavior for Anxiety in Hemodialysis Patients - Imas Sartika; Dewi Nur Puspita Sari (Sarana Ilmu Indonesia (Salnesia), 2026)
Chronic kidney disease (CKD) is a progressive, incurable condition that requires lifelong renal replacement therapy, one of which is hemodialysis. Patients undergoing hemodialysis often experience varying degrees of anxiety, necessitating interventions to help manage it. This study aimed to analyze the effect of progressive muscle relaxation therapy and health education based on the Theory of Planned Behavior on anxiety levels in chronic kidney failure patients undergoing hemodialysis at AN-Nisa Hospital. The study used a quantitative method with the Depression Anxiety and Stress Scale (DASS) questionnaire to measure anxiety levels. The intervention was provided through progressive muscle relaxation therapy and health education using standard operating procedures (SOPs) and leaflets compiled based on the Theory of Planned Behavior. Data analysis was performed using the Wilcoxon test. The results of the univariate analysis showed that after the intervention, most subjects did not experience anxiety, namely 32 subjects (97.0%). The Wilcoxon test results in the intervention group showed a p-value of <0.001 (p < 0.05), indicating a significant effect of the intervention on reducing anxiety. Research findings indicated that a combination of progressive muscle relaxation therapy and health education based on the Theory of Planned Behavior effectively reduces anxiety levels in patients with chronic kidney disease undergoing hemodialysis. This intervention can be considered as a nursing approach to managing anxiety in hemodialysis patients.